Payment for environmental services as a mechanism for promoting rural development in the upper watersheds of the tropics - Estrada, R.D.; Quintero, Marcela; Moreno, Alonso; Ravnborg, Helle Munk (CGIAR Challenge Program on Water and Food, 2009)
The project “Payment for environmental services as a mechanism for promoting rural development in the upper watersheds of the tropics” aimed to investigate and analyze the environmental externalities as a driver to promote social investment and a new dynamic and harmonic development in the rural sector. The environmental externalities were primarily waterrelated, which were quantified for selected Andean pilot watersheds. In these sites, the areas with higher potential to generate positive environmental externalities (environmental services) were prioritized. Moreover, in the prioritized areas the social and economic benefits (including multiplier effects by additional employments and income generated) derived from proposed land use changes to deliver environmental services were also assessed. Through the development of this project, the research team developed a methodological approach for quantifying and valuating the environmental services. Based on early results, the project through its development partners, Contents CPWF Project Report Page | 3 make direct investments in the selected watersheds to test if financial or economic mechanisms (e.g. PES) were viable and feasible for providing environmental services under the existing socioeconomic context. Between 2005 and 2008, the socioeconomic conditions changed drastically in the Andean region posing new challenges for the design and development of these financial mechanisms. This influenced the potential of environmental services as drivers of new rural. The project learned that private profitability of delivering these services is related to the type of watershed, and in general is low though can produce very high social benefits. When investment on infrastructure measures is proposed for improving a water-related environmental externality, this is rarely profitable at private prices. In most cases the investment is recouped by agricultural producers that not necessarily are the ones capturing the highest share of derived benefits and those sectors that do, do not contribute to pay back the investment cost neither compensate for the associated environmental benefit.